Penyuluhan Penangan Tobacco Mosaic Virus Pada Tanaman Tembakau Dan Pelatihan Pembuatan Limbah Dari Batang Tembakau - chusnul chotimah; Waslah, Waslah; Sholikhah, Lia Istiqomatus Sholikhah; Azulfa, Nawwal Azulfa; Rodhiyana, Siti Sofa Rodhiyana; Anggraini, Sofiah Anggraini; Jalil, Abdul Jalil; Wafa, M. Aliyul; Hartanti, Dyah Ayu Sri (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
Tobacco is a plantation plant originating from the genus Nicotiana, its leaves are used as the main raw material for making cigarettes. Tobacco is often infected with a disease/virus called Tobacco mosaic virus (TMV), a virus that attacks eggplant species. On tobacco plants, this virus causes yellow spots, resulting in less than-optimal harvest yields for the residents of Katemas Village. Therefore, researchers provide training to create systemic resistance, one of which is characterized by Pathogenesis Related Protein, which aims to fight viruses that attack tobacco so farmers can harvest optimally. The approach method for implementing community service for farmer groups uses the Service Learning method and the results achieved in this research are the manufacture of virus medicine for tobacco.